The Habit Formation trial of behavioral economic interventions to improve statin use and reduce the risk of cardiovascular disease: Rationale, design and methodologies. (August 2019) - Putt, Mary E; Reese, Peter P; Volpp, Kevin G; Russell, Louise B; Loewenstein, George; Yan, Jiali; Pagnotti, David; McGilloway, Ryan; Brennen, Troyen; Finnerty, Darra; Hoffer, Karen; Chadha, Sakshum; et al.
Background: Low adherence to statin (HMG-CoA reductase inhibitors) medication is common. Here, we report on the design and implementation of the Habit Formation trial. This clinical trial assessed whether the interventions, based on principles from behavioral economics, might improve statin adherence and lipid control in at-risk populations. We describe the rationale and methods for the trial, recruitment, conduct and follow-up. We also report on several barriers we encountered with recruitment and conduct of the trial, solutions we devised and efforts we will make to assess their impact on our study. Methods: Habit Formation is a four-arm randomized controlled trial. Recruitment of 805 participants at elevated risk of atherosclerotic cardiovascular disease with evidence of sub-optimal statin adherence and low-density lipoprotein (LDL) control is complete. Initially, we recruited from large employers (Employers) and a national health insurance company (Insurers) using mailed letters; individuals with a statin Medication Possession Ratio less than 80% were invited to participate. Respondents were enrolled if a laboratory measurement of low-density lipoprotein was >130 mg/dL. Subsequently, we recruited participants from the Penn Medicine Health System; individuals with usual-care low-density lipoprotein of >100 mg/dL in the electronic medical record were recruited using phone, text, email, and regular mail. Eligible participants self-reported incomplete medication adherence. During a 6-month intervention period, all participants received a wireless-enabled pill bottle for their statins and daily reminder messages to take their medication. Principles of behavioral economics were used to design three financial incentives, specifically a Simple Daily Sweepstakes rewarding daily medication adherence, a Deadline Sweepstakes where participants received either a full or reduced incentive depending on whether they took their medication before or after a daily reminder or Sweepstakes Plus Deposit Contract with incentives divided between daily sweepstakes and a monthly deposit. Six months post-incentives, we compared the primary outcome, mean change from baseline low-density lipoprotein, across arms. Results and lessons learned: Health system recruitment yielded substantially better enrollment and was cost-efficient. Despite unexpected systematic failure and/or poor availability of two wireless pill bottles, we achieved enrollment targets and implemented the interventions. For new trials, we will routinely monitor device function and have contingency plans in the event of systemic failure. Conclusion: Interventions used in the Habit Formation trial could be translated into clinical practice. Within a large health system, successful recruitment depended on identification of eligible individuals through their electronic medical record, along with flexible ways of contacting these individuals. Challenges with device failure were manageable. The study will add to our understanding of optimally structuring and implementing incentives to motivate durable behavior change.